Generalized autoregressive score model with high‐frequency data for optimal futures hedging. Issue 12 (8th August 2021) - Lai, Yu‐Sheng
Abstract: This study compares the performance of hedged equity index portfolios constructed using either a generalized autoregressive score (GAS) or a realized GAS (GRAS) model. GAS models encompass popular models, and studies indicate that high‐frequency data improve a model's forecasting ability. The in‐sample estimation results demonstrate that the GRAS model has better explanatory power and more robust time‐varying variance and dependence parameters when fat‐tailed distributions are accounted for. The out‐of‐sample comparison confirms its superiority in reducing hedged portfolio variance and accruing economic benefits to highly risk‐averse hedgers.